2021
DOI: 10.3389/fpsyt.2021.712492
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Sex- and Gender-Sensitive Research in Public Mental Health During the First Wave of the COVID-19 Crisis

Abstract: Background: Sex and gender are important modifiers of mental health and behavior in normal times and during crises. We investigated whether they were addressed by empirical, international research that explored the mental health and health behavior ramifications after the onset of the COVID-19 pandemic.Methods: We systematically searched the databases PsyArXiv, PubMed, PsycInfo, Psyndex, PubPsych, Cochrane Library, and Web of Science for studies assessing mental health outcomes (main outcomes) as well as poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 123 publications
(162 reference statements)
6
26
1
9
Order By: Relevance
“…On the other side, there was only one interaction effect, which was between time and gender for anxiety: while male students’ anxiety scores increased during the pandemic, female students’ scores remained at the same level (small effect). Altogether, contrary to previous studies 8 , 20 and to our hypotheses, the absence of interactions indicated that neither the mental distress of female nor non-medical students increased more than male or medical students’ distress. The interaction between anxiety and gender even indicated the opposite effect, namely that male students’ anxiety increased more than female students’ anxiety during the pandemic.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…On the other side, there was only one interaction effect, which was between time and gender for anxiety: while male students’ anxiety scores increased during the pandemic, female students’ scores remained at the same level (small effect). Altogether, contrary to previous studies 8 , 20 and to our hypotheses, the absence of interactions indicated that neither the mental distress of female nor non-medical students increased more than male or medical students’ distress. The interaction between anxiety and gender even indicated the opposite effect, namely that male students’ anxiety increased more than female students’ anxiety during the pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…Female versus male and also non-medical versus medical students reported more mental health issues (depression, anxiety, somatic complaints), consistent with previous findings regarding gender 6 8 and field of study 20 . Previous findings comparing medical and non-medical students regarding depression have been inconclusive 32 , and it must be considered that medical students may become socialized to disclaim mental health problems during their training 33 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition to that, population-based studies investigating the mental health situation in the context of the pandemic have included predominantly female samples [ 37 , 38 , 39 ], which limits a more comprehensive identification of the magnitude of the problem and, consequently, restricts the adoption of coping measures to a specific audience. In this context, this study contributes to overcoming this gap in scientific knowledge based on the research and appreciation of aspects related to the male population, which permeate the subjectivities and the social, symbolic, psychological, and psycho-emotional constructions of the population and their repercussions on health [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%